GAMBARAN PERILAKU KESELAMATAN WISATA WAHANA AIR OLEH PENGELOLA DI TANJUNG BENOA - Nyoman Adi Artha; Kadek Eka Swedarma; Komang Menik Sri Krisnawati (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
The behavior of water sport tourism managers in the effort of tourist safety is a behavior which involves knowledge, attitudes, and actions of water sport tourism managers in an effort to maintain the safety of tourists when playing water sport. The safety of tourists depends on the manager, which includes knowledge, attitudes, and actions. The purpose of this study is to know the description of the knowledge, attitudes, and actions of water sport tourism managers in Tanjung Benoa in an effort to maintain tourist safety. This research is a descriptive study with a quantitative method consisting of 38 samples obtained through purposive sampling. Data collection is done by distributing questionnaires to find out the description of knowledge, attitudes, and actions. Based on the results of the study the results obtained on the knowledge variable has a percentage of good knowledge that is 86.8% and sufficient knowledge of 13.2%. On the attitude variable the percentage of respondents who have good attitudes is 86.8% and bad attitude is 13.2%. Respondents in the action variable had a percentage of good actions is 81.6% and bad actions 18.4%. Therefor it can be concluded that the water sport tourism manager in Tanjung Benoa has good behavior because more than 81% get good grades in each variable. Suggestions for managers of water sport are consistent & sustainable in conduct training to all managers in order to maintain and improve the behavior of managers.